Implementasi Kurikulum 2013 (K13) Bahasa Arab di MTs Swasta Al-Hikmah Mogutat Kotamobagu - Solihah, Mamluatu; Fitrah, Moh. Aldi; Hidayah, Fathi; Wijaya, Mu’alim (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This study aims to fill the gap in the analysis of the implementation of the 2013 Curriculum (K13) for Arabic language at MTs Al-Hikmah Mogutat Kotamobagu and to identify the challenges faced in its execution. A qualitative approach with a case study design was used to allow for an in-depth understanding of the implementation process, the obstacles encountered, the supporting factors, as well as the results and recommendations for improvement. The research was conducted in 2023-2024, with the research subjects including Arabic language teachers and other related parties at the school. Data were collected through in-depth interviews and document collection, such as syllabi and lesson plans (RPP). Data analysis followed the Miles, Huberman, and Saldaña model, which consists of three stages: data collection, data condensation, and verification/conclusion drawing. The research findings reveal that MTs Swasta Al-Hikmah Mogutat Kotamobagu chose to retain the 2013 Curriculum (K13) despite the introduction of the Merdeka Curriculum, citing reasons such as resource readiness, educator competence, and student preparedness. The implementation of Arabic language teaching at MTs Al-Hikmah involves various teaching methods, such as the Toriqoh Al-Samiyah Al-Syafawiyah, Jigsaw Method, and interactive methods like singing and games. This approach reflects the teachers' efforts to adapt teaching methods to the students' needs and the curriculum in place. However, the study also found several challenges in curriculum implementation, including limitations in facilities, student abilities, and challenges in applying innovative teaching methods.